2021
DOI: 10.1111/sji.13108
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of myeloid‐derived suppressor cells with C‐reactive protein, ferritin and lactate dehydrogenase levels in patients with severe COVID‐19

Abstract: The novel coronavirus disease 2019 (COVID‐19) remains a global health emergency, and understanding the interactions between the virus and host immune responses is crucial to preventing its lethal effects. The expansion of myeloid‐derived suppressor cells (MDSCs) in COVID‐19, thereby suppressing immune responses, has been described as responsible for the severity of the disease, but the correlation between MDSC subsets and COVID‐19 severity remains elusive. Therefore, we classified patients according to clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…A recent study reported a significant correlation between C-reactive protein, ferritin, and lactate dehydrogenase levels and MDSC in patients with COVID-19. This indicates that immature PMN-MDSCs are associated with disease severity (102). Expansion of PMN-MDSCs and immature neutrophils in severe COVID-19 conditions indicates Th1 cell suppression and an increase in the frequency of Th17 cells due to strong polar migration to Th17 cells (103).…”
Section: Pmn-mdscs In Covid-19mentioning
confidence: 99%
“…A recent study reported a significant correlation between C-reactive protein, ferritin, and lactate dehydrogenase levels and MDSC in patients with COVID-19. This indicates that immature PMN-MDSCs are associated with disease severity (102). Expansion of PMN-MDSCs and immature neutrophils in severe COVID-19 conditions indicates Th1 cell suppression and an increase in the frequency of Th17 cells due to strong polar migration to Th17 cells (103).…”
Section: Pmn-mdscs In Covid-19mentioning
confidence: 99%
“… No change in e-MDSC (proportion) No [ 2 ] 14 N = 58 (COVID-19: 13 moderate, 37 severe; HD: 8) PB No Fresh M-MDSC: HLA-DR -/dim CD11b + CD14 + CD15 − PMN-MDSC: HLA-DR -/dim CD11b + CD14 − CD15 + Increase in M-MDSC and PMN-MDSC (proportion, in patients as compared to HD) No [ 84 ] 15 N = 26 (COVID-19: 13 convalescent; HD: 13) PB Yes Fresh M-MDSC: Lin − HLA-DR -/dim CD11b + CD14 + CD15 − PMN-MDSC: Lin − HLA-DR -/dim CD11b + CD14 − CD15 + e-MDSC: Lin − HLA-DR − CD11b + CD14 − CD15 − Increase in PMN-MDSC (proportion, in convalescent patients as compared to HD). No change in M-MDSC and e-MDSC (proportion) Inhibition of antigen-nonspecific T cell proliferation [ 68 ] 16 N = 67 (COVID-19: 26 mild, 15 severe; HD: 26) PB Yes Fresh M-MDSC: HLA-DR − CD11b + CD66b − CD14 + CD15 − PMN-MDSC: HLA-DR − CD11b + CD66b + CD14 − CD15 + Increase in M-MDSC and PMN-MDSC (proportion, in patients as compared to HD; increase in PMN-MDSC in mild patients as compared to severe patients) No [ 70 ] 17 N = 120 (COVID-19: 27 mild, 47 severe, 46 deceased) PB No Fresh M-MDSC: HLA-DR − CD14 + Increase in M-MDSC (proportion, in deceased patients as compared to mild and severe patients) No [ 3 ] 18 N = 80 (COVID-19: 40 ICU discharged, 40 ICU deceased) PB No Fresh <...>…”
Section: Mdscs In Covid-19mentioning
confidence: 99%
“…Intriguingly, while some studies reported a substantial increase in both circulating M-MDSC and PMN-MDSC subpopulations [ 2 , 63 , 64 , 70 ], other studies failed to identify M-MDSCs in either mild, moderate, or severe COVID-19 patients at different observation time points [ 67 , 71 ]. Takano et al found an elevated frequency of PMN-MDSCs but no M-MDSCs in severe COVID-19 [ 72 ].…”
Section: Mdscs In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations